Investors Legitimate Expectations and the Interests of the Host State in Foreign Investment - Asqari, Zeinab (Asian Economic and Financial Review, 2014)
Protection of investor’s legitimate expectations is one of the commitments that international investment law impose on host states. Though this commitment is not stated directly in treaty texts, but arbitration case law has distinguished it as an inseparable element of a fair and equitable treatment standard. The idea of legitimate expectations is trying to support the stability and predictability of the legitimate space of the host country. However, legitimate expectation is not an abstract concept and each hypothesis is meaningful in special situations. For a fair and equitable treatment, it is necessary that the legitimate expectations of the investor be Proportionate against general interests of the host state, legislation rights of the state and so on.